MAPPING OF LAND USE CHANGES IN THE CORE ZONE OF PARANGTRITIS SAND DUNES USING OBIA METHOD 2015-2020 - Latifa Melani Putri; Pramaditya Wicaksono (Universitas Negeri Medan, 2021)
Indonesia has many types of unique and rare landforms, one of which is sand dunes, which is located in Parangtritis. Sand dune has the main function as a conservation area, natural wall for the tsunami disaster, water catchment area, and habitat for sand dune flora and fauna. However, the existence of sand dunes is currently threatened with extinction due to the decrease in their area, which is caused by changes in land use. Every year, the land use in the Parangtritis sand dune changes. Therefore, it is important to map land use changes to determine the changes that occur in the sand dune core zone. This study aims to map land use change in the core zone of sand dunes using small format aerial images and the OBIA (Object-Based Image Analysis) method. Land use in the study area is classified into nine classes, namely sand dunes, dry land forest, shrubs, coastal shoals, open field, built-up area and settlements, dry land agricultural fields, roads, and fishponds. The results showed that there were changes in all land use classes. Based on the accuracy assessment, the overall accuracy for 2020 was 68.95%, while the classification results for 2015 were 61.81%.Keywords: land use changes, OBIA, Small Format Aerial PhotographyIndonesia memiliki banyak jenis bentuklahan yang unik dan langka, salah satunya adalah gumuk pasir yang terletak di wilayah Parangtritis, Daerah Istimewa Yogyakarta. Gumuk pasir memiliki fungsi utama sebagai kawasan konservasi, tembok alami bencana tsunami, kawasan resapan air, serta habitat untuk flora fauna gumuk pasir. Namun, keberadaan gumuk pasir saat ini terancam punah oleh adanya penurunan luasannya, yang disebabkan oleh perubahan penggunaan lahan. Setiap tahun, penggunaan lahan di gumuk pasir Parangtritis mengalami perubahan, yang akhirnya menyebabkan luasan gumuk pasir selalu berkurang setiap tahunnya. Oleh karena itu, pemetaan perubahan penggunaan lahan penting untuk dilakukan untuk mengetahui perubahan yang terjadi di zona inti gumuk pasir. Penelitian ini bertujuan untuk memetakan perubahan penggunaan lahan di zona inti gumuk pasir menggunakan foto udara format kecil dan metode OBIA (Object-Based Image Analysis). Penggunaan lahan di wilayah kajian diklasifikasikan menjadi sembilan kelas yaitu gumuk pasir, hutan lahan kering, semak belukar, beting pantai, lahan terbuka, lahan terbangun dan permukiman, ladang, jalan dan tambak. Hasil penelitian menunjukkan adanya perubahan pada semua kelas penggunaan lahan. Berdasarkan uji akurasi, akurasi keseluruhan (overall accuracy) hasil klasifikasi penggunaan lahan tahun 2020 sebesar 68,95%, sedangkan hasil klasifikasi penggunaan lahan tahun 2015 sebesar 61,81%.Kata kunci: Perubahan Penggunaan Lahan, OBIA, Foto Udara Format Kecil